Задачник по физико-химическим методам анализа: учебное пособие - Ляликов Ю. С. Юрий Сергеевич; Булатов М. И. Михаил Ильич; Бодю В. И. Валерий Иванович; Крачун С. В. Светлана Витольдовна (Москва, Мир, 1974)
Книга на английском языке